Role of serum Cystatin C as a marker of early nephropathy in metabolic syndrome: a case control study - Goel, Hemant; Aggarwal, Onam; Kumar, Anuj; Lali, Pramod; Chandra, Lal (International Journal of Research in Medical Sciences, 2018)
Background: The metabolic syndrome (MS) has become a significant public health problem and patients with MS are at higher risk for developing renal diseases. Serum Cystatin C suggested as a sensitive endogenous marker than creatinine for slight changes in GFR could be useful marker in MS. Methods: A total of 200 subjects were included. New International Diabetes Federation (IDF) definition of MS was used as inclusion criteria. Patients excluded were those with hypo/hyperthyroidism, on glucocorticoids, statins and fibrate, malignancy, cirrhosis, active liver disease and conditions affecting abdominal girth. Serum Cystatin C, insulin, creatinine, triglycerides, high density lipoproteins-cholesterol (HDL-C), fasting glucose, Urinary microalbumin and Urinary creatinine were estimated by standard method. eGFR and HOMA-IR (homeostasis model assessment of insulin resistance) were calculated. The primary outcome assessed was the occurrence of early nephropathy in MS and the secondary outcome included evaluation of early nephropathy by serum Cystatin C and eGFR. Appropriate statistical test was applied by using SPSS Version 21 software. Results: Fasting insulin levels and insulin resistance were significantly raised in MS cases. eGFR (MDRD) was lower in the MS cases (72.59±8.79mL/min/1.73m2) vs non-MS (130.34±40.75 mL/min/1.73m). Urinary microalbumin levels and serum cystatin C were significantly increased in MS and the cystatin c levels showed significant positive correlation with urinary microalbumin and negative correlation with eGFR.eGFR was found to be lower in the microalbuminuric than normoalbuminuric groups. Conclusions: Serum Cystatin C levels are higher in MS and can be useful, practical, non-invasive biomarker for evaluation of early renal involvement in MS.